Customer experience management in capsule hotels: a content analysis of guest online review - Olorunsola, Victor Oluwafemi; Saydam, Mehmet Bahri; Lasisi, Taiwo Temitope; Eluwole, Kayode Kolawole (Emerald Group Publishing Ltd, 2023)
PurposeCapsule hotels are a revolutionary Japanese concept of lodging that dates back over four decades. On the other hand, capsule hotels are a relatively new concept for most travelers outside of Japan. Organizations within this target segment are starting to recognize the critical role that an excellent customer experience management (CEM) strategy offers in improving competitiveness and organizational success. Thus, this research provides scholastic insight into the framework of CEM by evaluating the user-generated content at capsule hotels.Design/methodology/approachThis study inspected 1,304 online user-generated content from the top 10 capsule hotels from Booking.com. Leximancer 4.5 was deployed to analyze the data.FindingsThe analyses revealed nine key themes to CEM of capsule hotels which are staff, hotel, area, location, bed, capsule, check-in, noisy and luggage.Practical implicationsThis research encourages hospitality and tourism executives to develop specific strategies for capsule hotels.Originality/valueThis research differs from previous writings in that it attempts to fill a gap in the research by offering insight into the issue in the low-budget hotel industry and by identifying key indicators that influence customer experience.
Keywords: Capsule hotel; Customer experience; Customer experience management; Content analysis; Leximancer